Economic evaluations of interventions focusing on child abuse and neglect in high-income countries: a systematic review - Kugener, Tom; Wiethoff, Isabell; van Mastrigt, Ghislaine; van den Berg, Bram; Evers, Silvia M. A. A. (Frontiers in Psychiatry, 2023)
Introduction: Child abuse and neglect are together considered to be an important public health problem with a high individual and societal burden. Different interventions have been developed to prevent, diagnose, or treat maltreatment. While their effectiveness has been synthesized in prior reviews, the analysis of their cost-effectiveness is less common. The aim of this study is to synthesize and analyze economic evaluations of interventions focusing on child abuse and neglect in high-income countries. Methods: A systematic literature review was performed using MEDLINE, EMBASE, EconLit, PsycInfo and NHS EED. This study follows the PRISMA guidelines and double scoring was performed. The review includes trial- and model-based economic evaluations of preventive, diagnostic, and treatment related interventions in children up to 18 years or their caregivers. Risk of bias was assessed using the CHEC-extended checklist. The results are presented in a cost-effectiveness plane. Results: Of 5,865 search results, the full texts of 81 were analyzed, resulting in the inclusion of 11 economic evaluations. Eight of the included studies focus on prevention of child abuse and neglect, one study on diagnosis, and two on treatment. The heterogeneity between studies did not allow for the quantitative pooling of results. Most interventions were cost-effective, with the exception of one preventive and one diagnostic intervention. Conclusions: This study was subject to some limitations, as no grey literature was included, and the selection of studies may have been arbitrary due to varying terminologies and methodologies in the field. However, the quality of studies was high, and several interventions showed promising results.